Mengintegrasikan Metode Collaborative dan Discovery: Cara Baru dalam Pengajaran Bahasa - Hasri Fendi; M. Aries Taufik; Rahmi Eka Putri; Dian Anggraini; Imam Hanafi; Fenny Ayu Monia (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This study is conceptual research. It outlines the integration of collaborative model and discovery methods in language teaching. This concept has an advantage that it stimulates students to construct new knowledge through a collaborative and explorative way. This study discusses about the model of collaborative discovery method in which this model involves students to explore the knowledge both individually and in groups. The collaboration of individual and group study will encourage students’ active participation in learning. The model of collaborative discovery method becomes an ideal choice in language teaching.